Xanthophyll cycle-related non-photochemical quenching protects Sargassum thunbergii from high light-induced photoinhibition - Nan, Guo-Ning; Zhou, Xiao-Qun; Zhang, Xiu-Mei; Zhang, Quan-Sheng; Hu, Zi-Min; Huang, Rui-Ping; Zhang, Di (Frontiers in Marine Science, 2022)
As a common macroalga living in the intertidal zone, Sargassum thunbergii (Sargassaceae, Phaeophyta) is often exposed to drastic changes in solar photosynthetically active radiation during a diel cycle, the potential photosynthetic adaptation processes thus deserve attention. In this work, we examined the photosynthetic performance and xanthophyll cycle activity of this alga in response to high light. As exposed to high light condition (1200 μmol photons m-2 s-1, the average in-situ light intensity during noon time), a rapid decrease of effective quantum yield of photosystem II (YII) indicated an occurrence of photoinhibition, the corresponding increase of non-photochemical quenching indicated an existence of energy-dissipating cycles. After turning off the light, the value of YII gradually increased to 0.7 and NPQ gradually decreased, however, even after 80 mins recovery, no complete recovery was observed on NPQ and its value maintained at ~4. By using High-Performance Liquid Chromatography, the xanthophyll cycle pigments pool size was quantized as ~16 mol mol−1 Chl a × 100, and the activity of xanthophyll cycle, characterized by a de-epoxidation state (DPS), could reach up to ~0.5. Such large pigments pool size and rapid de-epoxidation of violaxanthin were supposed to allow S. thunbergii to induce high values of NPQ (~10). These results were further complemented by inhibitor (dithiothreitol, DTT) and pre-illumination experiments, showing 1) both the NPQ and xanthophyll cycle could be inhibited by DTT, and there was always a strong positive correlation between NPQ and DPS; 2) the previously formed antheraxanthin exhibited a long retention time and a slow epoxidation; 3) the long retention of antheraxanthin contributed to rapid accumulation of zeaxanthin, which should be responsible for the sustained NPQ under darkness condition. In conclusion, our present study demonstrated that the xanthophyll cycle induced NPQ could significantly protect S. thunbergii from high light.